PENINGKATAN KEMAMPUAN MEMBACA INTENSIF DAN KEMAMPUAN BERPIKIR ANALITIK DENGAN METODE GIST (GENERATING INTERACTION SCHEMATA AND TEXT) MELALUI PENDEKATAN SAINTIFIK - Triska Fauziah Resmiati (Tunas Siliwangi, 2016)
This research is motivated main problems the low capacity of intensive reading and analytical thinking skills of students. This is evident from the number of students who have not been able to understand the content of reading because it is difficult to find the main idea of the paragraph, the inability to organize a summary of the content of reading, and weakness to deduce the content of reading in learning activities intensive reading. This resulted in a lower speed reading effectiveness, which led to the low level of students' understanding of the content of reading. This study aimed to get a picture of the influence of methods of GIST through a scientific approach to improving the ability of intensive reading and analytical skills for students of the fifth grade of primary school. The method is carried out in the study is an experimental method of quasi or quasiexperiment that is used to seek treatment effect of utilizing methods GIST approach scientifically to increase the ability of intensive reading and analytical skills of students in the form of experimental design used is the development of a pure experiment (true experiment design ) using a pretest-posttest control group design. The experimental group was treated (treatment) using the method of GIST through a scientific approach, while the control group was not given a similar treatment. Final test (posttest) are provided in two classes to determine the effectiveness of the treatment. As for the process of learning to do in the experimental class, used observation sheet. The results of the data pre-test, post-test, and N-gain quantitatively tested with a test average difference nonparemetrik manwithney. Based on the analysis, it can be concluded that the increase in the ability of intensive reading and analytical skills of students gained from learning to apply the scientific method of GIST through approach is better than learning terlangsung.Keywords: Method of GIST through Scientific Approach, Intensive Reading Ability, Capability Analysis.